CONTROL AND ANALYSIS OF AIRPLANE SYSTEMS AND COMPONENTS RELIABILITY DURING THEIR OPERATION - Кучер, О.; Власенко, П. (Science-based technologies, 2010)
The main concepts of airplane systems and components reliability control during their operation were considered.The standards for reliability control of aviation technique were proposed. Two types of control levels wereconsidered. The method of variance analysis for reliability control of aviation technique was proposed. The resultsof reliability control, taken from automated system, are shown.